Rekonstruksi Prinsip Hubungan Internasional dalam Tatanegara Islam: Antara Normativitas Klasik dan Realitas Global Kontemporer - Ghina Ghefira Fadhia Arham; Muhammad Afif Al Husen; Muhammad Afdal Amirullah3, Amirullah; Kurniati Kurniati (Indo Publishing, 2026)
The development of the modern international system, which emphasizes peace, state sovereignty, legal equality, and human rights, has created the need to re-examine the classical construction of international relations in Islamic statecraft. Concepts such as dār al-Islām, dār al-ḥarb, jihad, and classical citizenship systems emerged within the historical context of the caliphate, which differs significantly from the modern nation-state system. This study aims to analyze the principles of international relations in Islamic governance, identify their opportunities and challenges in contemporary global realities, and formulate a contextual and relevant reconstruction. This research employs a literature review method with a normative-conceptual approach by examining primary sources such as the Qur'an, Sunnah, classical works of fiqh siyasah and siyar, as well as secondary sources including scholarly journals, monographs, and international legal documents. The findings indicate that universal Islamic values such as justice, peace, respect for treaties, and public welfare are highly relevant to modern international law. However, several classical constructions require reinterpretation to align with principles of state sovereignty, human rights, and equal citizenship. Therefore, the maqāṣid al-syarī‘ah approach serves as the main instrument for reconstructing Islamic international relations so that it remains relevant, adaptive, and capable of contributing to the contemporary global order.